Bail-out unexpanded stent implantation in acute left main dissection treated with intra coronary lithotripsy: a case report. Issue 4 (8th October 2019) - Tumminello, Gabriele; Cavallino, Chiara; Demarchi, Andrea; Rametta, Francesco
Abstract: Background: The percutaneous treatment of heavily calcified coronary lesions is challenging and presents high rate of complications. Unexpandable stent is one of the most serious complication. Both of these conditions may benefit from the intracoronary lithotripsy (ICL-Shockwave ® ), a new coronary percutaneous technique. Case summary: This case report describes a man treated with percutaneous coronary intervention (PCI) for a left main (LM) severe calcified lesion. The PCI was complicated by a huge dissection of LM in a not completely expandable lesion. A bail-out stent implantation was performed with residual unexpansion. The ICL permitted to expand acutely the stent and obtain an optimal final result. Discussion: Familiarity with dedicated techniques and devices to treat calcified coronary lesions is fundamental to perform high-risk complex PCI. This case emphasizes the potential usefulness of the new ICL technique to treat calcified lesions or related complications like unexpandable stent.